School and parent prestige : school tradition in Indonesia and Philippines border society - Macpal, Sunandar (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper intends to answer why Kawaluso Island peoples have an orientation to send their children to a higher level. Kawaluso Island as one of the islands in the RI-Philippines border region, like other border areas, has problems in the field of education, both access and infrastructure. This study uses ethnographic methods as part of qualitative research making researchers as the main instrument. Data collection uses participatory observation where the researcher is involved in the activities of the community under study. The findings in this study are that school and prestige for parents (Kawaluso peoples) become discourses that cannot be separated from one and another. A form of recognition or prestige for parent, who are able to send their children to a higher level, is one of the practices of denial of economic practices. Nevertheless, the process of recognizing parents in achieving educational attainment by children, at the same time also benefits economically. The economic benefit in question is when Kawaluso residents who have finished school are able to carry out a process of vertical social mobility.